Idiosyncratic Risk : An Empirical Analysis, with Implications for the Risk of Relative-Value Trading Strategies - Richards, Anthony (Washington, D.C. : International Monetary Fund, 1999)
This paper models the idiosyncratic or asset-specific return of an asset as the return on a portfolio that is long in that asset and short in other assets in the same class, thereby removing the common components of returns. This is the type of 'hedged' position that is held by relative-value investors. Weekly returns data for seven different asset classes suggest that idiosyncratic risk is: higher at times of large return outcomes for the asset class as a whole; positively autocorrelated; and correlated across different asset classes. The implications for risk management are discussed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet